Prosumer capitalism in the sharing economy: a gender approach to service providers’ experiences in ridesharing platforms - Castillo-Villar, Fernando Rey; Castillo-Villar, Rosalia G.; Castillo-Villar, Krystel K. (Frontiers in Sociology, 2024)
The study draws on the theory of "prosumer capitalism" to explore the experiences of female drivers in ridesharing platforms. Twenty-five phenomenological in-depth interviews were carried out with Mexican female drivers in ridesharing platforms. The results yielded insights regarding the motives of women to become rideshare drivers, their prosumption experiences and gender issues related to the job. The study offers a novel gender-based approach to comprehend the status of female service providers as prosumer-as-producers and the diverse risks and challenges they face while working in the sharing economy. In a practical sense, platform designers and marketers can improve the application functions to attend to the specific needs of female drivers and implement inclusive measures to safeguard their integrity and well-being.